(Dis)Arming the madman: sane supremacy and the Second Amendment. Issue 7 (9th August 2018) - Procknow, Greg
Abstract: The protection of American mental health consumers' Second Amendment rights is the 'mad' liberation issue of the twenty-first century. Federal laws currently dispossess the differently minded of their Second Amendment access and rights to bear firearms. In response to a spate of school shootings, 'Red flag laws' are used in an effort to circumvent mad citizens' rights to self-preservation and defence. In this article I am proposing neither a political-left nor right side of the aisle position, but rather a bipartisan, anti-sanist stance, where I call for an end to America's contemporary era of sane supremacy that strips the mad citizenry of their rights to own firearms.